2010
DOI: 10.1177/0011000010378613
|View full text |Cite
|
Sign up to set email alerts
|

Do Principal Preparation Programs Influence Student Achievement Through the Building of Teacher-Team Qualifications by the Principal? An Exploratory Analysis

Abstract: Purpose:The primary purpose of this study is to explore how the characteristics of the principal preparation programs of newly hired elementary school principals might influence school achievement through the development of well-qualified teams of teachers by the school. Of primary interest is whether elementary school principals from preparation programs with certain types of characteristics are more or less likely to build teams of well-qualified teachers who, in turn, positively affect overall student achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 50 publications
3
63
0
5
Order By: Relevance
“…-Financial assistance: Financial assistance allows programs to recruit more selectively, target underrepresented populations, and recruit teachers who otherwise would not be able to take time away to participate in the program. • Summary of evidence: Two tier III studies (Braun, Gable, and Kite, 2008;Fuller, Young, and Baker, 2011) found positive correlations between participation in principal preparation programs and student achievement, teacher qualifications, and school culture; one tier IV logic model supported this finding .…”
Section: Principal Preparation Programsmentioning
confidence: 97%
See 2 more Smart Citations
“…-Financial assistance: Financial assistance allows programs to recruit more selectively, target underrepresented populations, and recruit teachers who otherwise would not be able to take time away to participate in the program. • Summary of evidence: Two tier III studies (Braun, Gable, and Kite, 2008;Fuller, Young, and Baker, 2011) found positive correlations between participation in principal preparation programs and student achievement, teacher qualifications, and school culture; one tier IV logic model supported this finding .…”
Section: Principal Preparation Programsmentioning
confidence: 97%
“…Sources: This summary describes recurring elements of principal preparation programs and not necessarily a specific program; see Darling-Hammond et al, 2007;Braun, Gable, and Kite, 2008;Fuller, Young, and Baker, 2011.…”
Section: Principal Preparation Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fuller, Young, and Baker (2011) and Orr and Orphanos (2011) examined the influence of principal preparation programs on student achievement. Orr (2011) studied the program experiences and career outcomes of graduates of leadership preparation programs.…”
Section: Content Analysis Of 2013 Spl Evaluation Proposalsmentioning
confidence: 99%
“…There are also many quality assessment studies done based on certain criteria (Goe & Stickler, 2008). However, the term 'quality teacher' is still considered unclear due to the absence of an agreement from the scholars on the definition and the dimensions that represent the quality teacher concept (Blanton et al, 2006;Burnett & Meacham, 2002;Fuller, Young, & Baker, 2010;Goe, 2007). According to Cavaluzzo (2004), there have been no agreements on the actions that contribute to quality teaching.…”
Section: Literature Review: Quality Teacher Conceptmentioning
confidence: 99%